Scenario with combined density and heating control to reduce the impact of the bootstrap current in Wendelstein 7-X. (27th September 2019) - Sinha, P.; Böckenhoff, D.; Endler, M.; Geiger, J.; Hölbe, H.; Smith, H.M.; Pedersen, T.S.; Turkin, Y.
Abstract: Wendelstein 7-X is a low-shear stellarator with an island divertor, formed by natural magnetic islands at the plasma edge and ten modular divertor units for particle and energy exhaust. For the island divertor concept to work properly, the device is optimized for small internal currents. In particular, the bootstrap current is minimized. Previous studies predicted a thermal overload of the targets at a particular location, due to the slow evolution of the toroidal net current in the initial phase of certain otherwise desirable high-power discharges. The present numerical study explores the neoclassical predictions for the bootstrap current in more detail and demonstrates, as a proof of principle, that a path from low density and low heating power to high density and full heating power exists, on which the bootstrap current remains constant. This offers the possibility to reach the predetermined toroidal net current at low heating power, where no overload will occur in the transient phase.